Peranan Efikasi Diri dan Kontrol Peranan Efikasi Diri dan Kontrol Diri Terhadap Prokrastinasi Akademik pada Mahasiswa di Universitas Muhammadiyah Sidoarjo: The Role of Self-Efficacy and Self-Control on Academic Procrastination of Students at Muhammadiyah University of Sidoarjo - Firmanti, Salwa Rosamarta; Affandi, Gozali Rusyid (Academia Open, 2026)
General Background: Academic procrastination is a prevalent behavioral issue in higher education that affects students’ task completion and academic responsibility. Specific Background: Psychological constructs such as self-control and self-efficacy are frequently associated with students’ tendencies to delay academic tasks. Knowledge Gap: Although prior studies have examined these variables separately, limited empirical evidence simultaneously analyzes their relationship with academic procrastination within a unified quantitative framework. Aims: This study aims to examine the relationship between self-control and self-efficacy with academic procrastination among university students. Results: The findings indicate that self-control and self-efficacy are significantly related to academic procrastination, showing that students with higher levels of self-regulation and confidence in their abilities tend to demonstrate lower procrastination behavior. Novelty: This study provides integrated empirical evidence highlighting the combined role of self-control and self-efficacy in explaining academic procrastination in a university context. Implications: The results suggest the importance of developing psychological interventions and academic guidance programs focusing on strengthening students’ regulatory capacity and personal belief systems to reduce procrastination tendencies in higher education settings. Keywords: Academic Procrastination, Self-Control, Self-Efficacy, University Students, Quantitative Study Key Findings Highlights: Higher regulatory capacity is associated with lower delay in completing academic tasks. Strong personal belief in academic ability corresponds to reduced postponement behavior. Both psychological variables jointly contribute to explaining student delay patterns.